2015
DOI: 10.1589/jpts.27.2713
|View full text |Cite
|
Sign up to set email alerts
|

Maximal lateral reaching distance on the affected side using the multi-directional reach test in persons with stroke

Abstract: [Purpose] This study aimed to examine the relationship between maximal lateral reaching distance on the affected side and weight shifting using the Multi-directional Reach Test in persons with stoke. [Subjects] Fifty-one chronic stroke participants were recruited from two rehabilitation hospitals. This study administered the Berg Balance Scale, Timed Up-and-Go, Trunk Impairment Scale, Modified Barthel Index and measured different maximal reaching distances. [Results] The maximal lateral reaching distance on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Instead, the TUG outcome is an objective, continuous parameter (as it measures the time) [ 32 ]. Nevertheless, [ 55 ] found a correlation between TIS and the reaching distance in the affected side in stroke survivors, but while performing the (standing) functional reach test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, the TUG outcome is an objective, continuous parameter (as it measures the time) [ 32 ]. Nevertheless, [ 55 ] found a correlation between TIS and the reaching distance in the affected side in stroke survivors, but while performing the (standing) functional reach test.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang and colleagues [ 55 ] suggested that, in stroke survivors, the kinematic results of the (standing) functional reach test along the contra and ipsilesional directions are correlated. In this study, we focused on the modified functional reach test in two directions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of this instrument is not feasible because the equipment needed is expensive and sophisticated. However, the Berg Balance Scale (BBS), the Time Up and Go (TUG), the Tinetti POMA scale, the Multidirection Reach Test (MDRT), the Lateral Reach Test (LRT), and the Functional Reach Test (FRT) are additional clinical measures that assess balance ( Lin et al, 2004 ; Blum & Korner-Bitensky, 2008 ; Canbek et al, 2013 ; Hwang et al, 2015 ). Among these tests, LRT, MDRT, and FRT are the most feasible tests because they can be done quickly and do not require any use of any complex or expensive equipment ( Duncan et al, 1990 ; Newton, 2001 ; Katz-Leurer et al, 2009 ; Deshmukh, Ganesan & Tedla, 2011 ; Hwang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Berg Balance Scale (BBS), the Time Up and Go (TUG), the Tinetti POMA scale, the Multidirection Reach Test (MDRT), the Lateral Reach Test (LRT), and the Functional Reach Test (FRT) are additional clinical measures that assess balance ( Lin et al, 2004 ; Blum & Korner-Bitensky, 2008 ; Canbek et al, 2013 ; Hwang et al, 2015 ). Among these tests, LRT, MDRT, and FRT are the most feasible tests because they can be done quickly and do not require any use of any complex or expensive equipment ( Duncan et al, 1990 ; Newton, 2001 ; Katz-Leurer et al, 2009 ; Deshmukh, Ganesan & Tedla, 2011 ; Hwang et al, 2015 ). FRT and LRT assess an individual’s potential to reach ahead or sideways, causing their center of mass (COM) to shift over a firm base of support (BOS), and assessing their ability to control their body ( Duncan et al, 1990 ; Newton, 2001 ; Katz-Leurer et al, 2009 ; Deshmukh, Ganesan & Tedla, 2011 ; Verheyden et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Functional reach (FR) is a very important motion because it is often performed in daily life. Furthermore, FR is used to evaluate postural control 1 , 2 , 3 , 4 , 5 ) . Duncan et al developed the FR test to evaluate the limits of stability 1 ) .…”
Section: Introductionmentioning
confidence: 99%